Assessment of the Proportionality of Religious Books Publication with People’s Expectations in Qom - Mohammad Javad Najafi; Reza Karimi (تحقیقات اطلاع‌رسانی و کتابخانه‌های عمومی, 2010)
Purpose: This research aims to investigate the proportionality of religious books publication with expectations of individuals in society. Methodology: The present study is carried out by survey method. To collect data, viewpoints of 807 persons among visitors of libraries and bookstores were gathered by questionnaire. Findings: The research findings indicated that the first priority of 55.5% of responders was books with religious subjects. Also, 48.7% of the population under study expressed that more than half of their reading is assigned to religious field. The places providing highest accessibility of people to religious books were bookstores and libraries with percentages of 50.4% and 32.1%, respectively. Taking advantage of internet was low in all educational levels, whereas use of bookstores was evaluated to be high in all educational levels. The majority of responders (87.6%) emphasized that the most significant feature of book appearance is its title. 90.8% of the population under study believe that the name of author and translator is the most important factor in publication of religious books. Furthermore, books by Shahid Motahhari, as well as books on the subject of religious figures, Imams, beliefs, hadith, and prayers were introduced as the most impressing ones. From the responders’ point of view, the most important drawbacks of religious books can be considered as being repetitious, not being documentary, frequent inexpressive Arabic terms, and not being proportional with the reader’s need. Also, they believe that the best strategies for advertising the religious books include advertisement through mass media, reducing the cost, proportionate them with present needs, and increasing the number of public and free libraries. The main expectations of the population under study from religious books included getting acquainted with history of religious figures, getting familiar with the most significant subject in Islam, valuable concepts in Nahjolbalagheh, and Karbala resurrection. In addition, major expectation of the responders from religious books was providing response for their questions, getting them familiar with fine religious issues, elucidating the requirements of a perfect man in modern era, and the ability to resolve the ambiguities in religion for young people. Originality/Value: Since religious books have assigned the highest publication level, it is necessary by precise planning to get sufficient understanding of readers of religious books and their needs. Through survey of the responders’ viewpoints, the present research can assist publishers of religious books in better planning for publication components.